WALI NIKAH BAGI PEREMPUAN YANG LAHIR KURANG DARI ENAM BULAN USIA PERKAWINAN DI IDI RAYEUK - Fadli, Fadli; Juliandi, Budi (TAHKIM, 2024)
This research is about marriage guardians for women born less than six months of marriage at Idi Rayeuk. This research is an empirical study using a sociological approach. However, the theoretical aspects remain put forward. There are three research questions here: First, how is the determination of marriage guardians by marriage officer in Idi Rayeuk for women born less than 6 months in Idi Rayeuk. Second, how is the determination of the six-month period of pregnancy by marriage officer in Idi Rayeuk. Third, what is the legal basis used by marriage officer in Idi Rayeuk in establishing marriage guardians and a six-month period for women born less than six months of marriage. The results showed that the determination of the guardian judge by marriage officer in Idi Rayeuk for women who were born less than six months from the marriage period was a compromise between positive law and the applicable law in the community, namely the Shafi'i school of fiqh, including the compromise between marriage officer in and the public. The family law becomes converted into a living law which is a compromise of some of the rules contained in positive law and the Shafi'i jurisprudence. Theoretically-practically, it is the wali hakim who acts as the guardian for women born less than six months of marriage as in the Shafi'i school of fiqh. Not a biological father. But in recording the name of the guardian, still includes the name of the biological father. Shafi'i Jurisprudence is carried out while still carrying out state rules, namely by recording it on the form containing the name of biological father. Keywords: marriage guardian, woman born less than 6 months, legal guardian